A novel KCNQ3 mutation in familial epilepsy with focal seizures and intellectual disability. (19th December 2014) - Miceli, Francesco; Striano, Pasquale; Soldovieri, Maria Virginia; Fontana, Antonina; Nardello, Rosaria; Robbiano, Angela; Bellini, Giulia; Elia, Maurizio; Zara, Federico; Taglialatela, Maurizio; Mangano, Salvatore
Summary Mutations in the KCNQ2 gene encoding for voltage‐gated potassium channel subunits have been found in patients affected with early onset epilepsies with wide phenotypic heterogeneity, ranging from benign familial neonatal seizures (BFNS) to epileptic encephalopathy with cognitive impairment, drug resistance, and characteristic electroencephalography (EEG) and neuroradiologic features. By contrast, only few KCNQ3 mutations have been rarely described, mostly in patients with typical BFNS. We report clinical, genetic, and functional data from a family in which early onset epilepsy and neurocognitive deficits segregated with a novel mutation in KCNQ3 (c.989G>T; p.R330L). Electrophysiological studies in mammalian cells revealed that incorporation of KCNQ3 R330L mutant subunits impaired channel function, suggesting a pathogenetic role for such mutation. The degree of functional impairment of channels incorporating KCNQ3 R330L subunits was larger than that of channels carrying another KCNQ3 mutation affecting the same codon but leading to a different amino acid substitution (p.R330C), previously identified in two families with typical BFNS. These data suggest that mutations in KCNQ3, similarly to KCNQ2, can be found in patients with more severe phenotypes including intellectual disability, and that the degree of the functional impairment caused by mutations at position 330 in KCNQ3 may contribute to clinical disease severity.